METODE CERITA DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA ARAB - Laily Fitriany; Karina Nur Aini (Faculty of Cultures and Languages UIN Raden Mas Said, 2020)
The method is a step or a way to make teachers assisted in conveying subject matter and to be able to achieve learning goals easily. However, if the method chosen is not in accordance with the subject matter, it will make it more difficult for students and teachers themselves. In this study aims to investigate / describe a story method that uses the formula 5w + 1h with the help of an image. In this study, the method implemented in this study is a descriptive-qualitative research method by collecting observation data and learning practices. The findings in this study show that there are advantages and disadvantages in using the story method. Here are the advantages of this story method, one of which is to be able to practice listening and speaking skills of learners. The listeners will get a positive impact, as well as getting a new vocabulary from the storyteller in front and the speaker can have the courage to speak in Arabic freely. While the lack of this method of this story, one of which is that it takes a long time to compile a story that is about to be presented.